Lyric Lines in Enhancing Students’ Reading Comprehension - Junaidi, Natasya Puteri; Sunarti, Sunarti (English Teaching and Linguistics Journal (ETLiJ), 2024)
This research aims to identify the significant effect of lyric lines to teach students’ reading comprehension. The population was a senior high school in Samarinda. This research employed a quasi-experimental design with treatment in a single group of students. The researchers used SPSS to analyse the data. To find out the result of the standard deviation and the main score of the variables in a single class, the data analysis procedure in this research used inferential statistics. The result showed that Lyric lines significantly enhanced the students’ reading comprehension that was given to a single class and the class had been treated twice, with and without song lyrics. The fact that the second post-test had a mean score (85,364) while this score was higher than first the post-test (76,364). Proved that the lyric lines gave a significant effect which post-test 2 post-test 1. The paired sample score showed the significant value (2-tailed) is 0.00 0.05. In the words, (Ho) was rejected and (Ha) was accepted. So, it can be concluded that there is a significant effect of using learning strategies of lyric lines in enhancing reading comprehension for English lesson.